Analysis of Powerline Channel Model for Communication from Primary Substation Node to End-Users - Anatory, Justinian; Mvungi, Nerey H.; Kissaka, Mussa (Winter-Spring, 2004)
Abstract—The low voltage power networks in developing countries like Tanzania are designed without taking into consideration their application in data communication. In order to use them for data communication, powerline channel models have been developed and analysed in order to understand the factors that will affect the transmission. In this paper transfer characteristics of powerline channel from power users to primary substation have been modeled and analyzed. Simulation results show that the signal in PLC environment attenuates more with interconnections, which needs to be amplified/regenerated within a few meters.
Keywords: Power-line channel; Communication